Prognostic Value of Heterogeneity Index Derived from Baseline 18F-FDG PET/CT in Mantle Cell Lymphoma - Liu, Fei; Gu, Bingxin; Li, Nan; Pan, Herong; Chen, Wen; Qiao, Ying; Song, Shaoli; Liu, Xiaosheng (Frontiers in Oncology, 2022)
Objectives: Mantle cell lymphoma (MCL) represents a group of highly heterogeneous tumors, leading to a poor prognosis. Early prognosis prediction may guide the choice of therapeutic regimen. Thus, the purpose of this study was to investigate the potential application value of heterogeneity index (HI) in predicting the prognosis of MCL. Methods: A total of 83 patients with histologically proven MCL who underwent baseline fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) were retrospectively enrolled. The clinicopathologic index and PET/CT metabolic parameters containing maximum and mean standard uptake value (SUVmax and SUVmean), metabolic tumor volume (MTV), total lesion glycolysis (TLG) and HI were evaluated. Receiver operating characteristic (ROC) curve analyses were performed to determine the optimal cutoff values of the parameters for progression-free survival (PFS) and overall survival (OS). Univariate and multivariate Cox regression were used to assess relationships between risk factors and recurrence. Kaplan-Meier plots were applied for survival analyses. Results: In univariate analyses, age (HR = 2.51, 95% CI = 1.20-5.24, P = 0.041 for body weight (BW)) and HI-BW (HR = 4.17, 95% CI = 1.00-17.38, P = 0.050) were significantly correlated with PFS. In multivariate analyses, age (HR = 2.61, 95% CI = 1.25-5.47, P = 0.011 for BW) and HI-BW (HR = 4.41, 95% CI = 1.06-18.41, P = 0.042) were independent predictors for PFS, not for OS. And B symptoms (HR = 5.00, 95% CI = 1.16-21.65, P = 0.031 for BW) was an independent prognostic factor for OS, but not for PFS. The other clinicopathologic index and PET/CT metabolic parameters were not related to outcome survival in MCL. Conclusion: The age and HI derived from baseline PET/CT parameters were significantly correlated with PFS in MCL patients.